2016
DOI: 10.1016/j.ejor.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Do ‘big losses’ in judgmental adjustments to statistical forecasts affect experts’ behaviour?

Abstract: a b s t r a c tThe behaviour of poker players and sports gamblers has been shown to change after winning or losing a significant amount of money on a single hand. In this paper, we explore whether there are changes in experts' behaviour when performing judgmental adjustments to statistical forecasts and, in particular, examine the impact of 'big losses'. We define a big loss as a judgmental adjustment that significantly decreases the forecasting accuracy compared to the baseline statistical forecast. In essenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…Franses and Legerstee (2011) found that a simple combination of forecasts outperformed both statistical and judgmentally adjusted forecasts. Petropoulos et al (2016) demonstrated that a 50‐50 combination of forecasts in the period after a manager's adjustments have resulted in significant losses can indeed increase accuracy by 14%. Wang and Petropoulos (2016) found that a combination is as good, if not better, than selecting between a statistical or an expert forecast.…”
Section: Literaturementioning
confidence: 99%
“…Franses and Legerstee (2011) found that a simple combination of forecasts outperformed both statistical and judgmentally adjusted forecasts. Petropoulos et al (2016) demonstrated that a 50‐50 combination of forecasts in the period after a manager's adjustments have resulted in significant losses can indeed increase accuracy by 14%. Wang and Petropoulos (2016) found that a combination is as good, if not better, than selecting between a statistical or an expert forecast.…”
Section: Literaturementioning
confidence: 99%
“…Behavioural issues have been on the forecasting research agenda for a long time, and typically studied under the area of judgemental forecasting. Petropulous, Fildes and Goodwin (2015) examine the effect of big losses on experts' behaviour when performing adjustments to statistical forecasts. The authors show how after a big loss, defined as a judgmental adjustment that significantly decreases the forecasting accuracy compared to the baseline statistical forecast, experts are more likely to make large adjustments in the opposite direction to the previous large error.…”
Section: Introduction To the Articles In The Special Issuementioning
confidence: 99%
“…For example, there is a stream of research that examines the work of expert modellers (Tako, 2014;Tako & Robinson, 2010;Waisel, Wallace, & Willemain, 2008;Willemain, 1994Willemain, , 1995 , novice modellers (S. G. Tavella & Papadopoulos, 2015b;, or both (Tavella & Papadopoulos, 2015a). Research focusing on other types of actors is also beginning to appear, such as studies of forecasting experts (Petropoulos, Fildes, & Goodwin, 2016;Syntetos, Kholidasari, & Naim, 2016), decision analysts (Papamichail, Alves, French, Yang, & Snowdon, 2007), and OR consultants proving strategy support (O'Brien, 2015).…”
Section: Focus On or Actorsmentioning
confidence: 99%